Public Health Risk of Arsenic Contamination in Food at Old Kahna, Lahore, Pakistan - TASKEEN, ABIDA; NAEEM, ISMAT; SIDDIQUE, ZEB (Asian Journal of Chemistry, 2010)
Poisoning from arsenic in drinking water is a very serious problem in Pakistan stressing the need for analysis of water, soil, food and other environmental samples to gauge the extent of risk posed to the health of general public and for remedial measures. Kahna (old) is a small locality of Lahore which was selected as a test site and drinking water samples and diverse food samples were collected randomly and analyzed for arsenic contents by arsenic testing kit and atomic absorption spectroscopy (graphite furnace). The arsenic amount in samples of drinking water (from sunken tube-wells installed in houses), milk, locally grown vegetables, mutton, beef, rice is 71 ppb, 13.50 ppb, 1.5, 1.6, 0.8, 3.7 and 0.3 mg/kg, respectively. Food values are under permissible levels but arsenic in water is much higher than standard thus exposing the population of Old Kahna at high cancer risk and other diseases.